Beyond chemistry: the role of employee emotional competence in personalized services. Issue 3 (8th February 2018) - Matute, Jorge; Palau-Saumell, Ramon; Viglia, Giampaolo
Abstract : Purpose: This paper aims to investigate how employees' emotional competences affect customers' responses in the context of emotional-driven and personalized services. Specifically, it proposes a model to analyze the influence of employees' emotional competence on rapport, trust and loyalty toward the service employee and the company. Design/methodology/approach: The empirical context to validate the proposed theory is the fitness realm. The sample comprises 296 clients from fitness personal training services. Data collection was carried out by means of personal surveys in three relevant fitness clubs in the city of Barcelona (Spain). The study uses partial least squares to test and validate the proposed theoretical model. Findings: Employee emotional competence (EEC) directly affects personal loyalty, trust toward the service employee and rapport. However, higher levels of emotional skills are not significantly associated with loyalty toward the company. The results also suggest that trust significantly enhances loyalty. Interestingly, high levels of rapport between the service worker and the employee could even damage the level of loyalty toward the company. Originality/value: Prior research documents that emotional intelligence enhances diverse positive customer outcomes, especially in emotionally charged interactions. Nonetheless, few studies have focused on analyzing how customers' perceptions about services employees' emotional skills are determining their attitudes and behavioral intentions. This study provides evidence on employee's influences on consumer behaviors and outcomes, with a specific focus on EEC. It also sheds light on the unintuitive impact of customer employee rapport on loyalty toward the company.